2022
DOI: 10.1007/s11187-022-00671-0
|View full text |Cite
|
Sign up to set email alerts
|

Openness to knowledge: does corporate social responsibility mediate the relationship between familiness and absorptive capacity?

Abstract: Being open to absorb external knowledge is a key competitive advantage for small- and medium-sized family firms. In this study, we propose and test a model in which corporate social responsibility is the key feature linking family-specific resources (i.e., familiness) to the family firm’s ability to absorb external knowledge. By integrating different theoretical perspectives, we argue that family firms use corporate social responsibility activities as signals to build trust and long-term relationships with int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 154 publications
(340 reference statements)
0
5
0
1
Order By: Relevance
“…By investing in environmental, social, and economic well-being, businesses develop an enduring relationship with consumers. This relationship promotes a positive association with impulsive purchasing [47]. Thus, we propose the following hypotheses: H1: Environmental well-being has a positive association with impulse buying.…”
Section: Sustainable Csr Practices and Impulsive Buying Intentionmentioning
confidence: 94%
“…By investing in environmental, social, and economic well-being, businesses develop an enduring relationship with consumers. This relationship promotes a positive association with impulsive purchasing [47]. Thus, we propose the following hypotheses: H1: Environmental well-being has a positive association with impulse buying.…”
Section: Sustainable Csr Practices and Impulsive Buying Intentionmentioning
confidence: 94%
“…Most researchers have found that where CSR is concerned, family firms behave differently to non-family firms (Cabeza-García et al, 2017 ; Cuadrado-Ballesteros et al, 2017 ; El Ghoul et al, 2016 ; Fehre & Weber, 2019 ; Izzo & Ciaburri, 2018 ) showing that family firms conduct more CSR activities than non-family firms (Faller and zu Knyphausen-Aufseß, 2018 ). The owning family provides the firm with a particular set of family resources: financial, human, or social capital to pursue its personal goals within the firm (Pütz et al, 2022 ; Weismeier-Sammer et al, 2013 ). Familiness describes the family resources integrated within the firm and is “the unique bundle of resources a particular firm has because of the system interaction between the family, its individual members, and the business.” (Habbershon & Williams, 1999 , p. 11).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Family firm research theorizes that family firms with significant levels of familiness combined with the firms’ resources will be able to achieve increased performance levels (Chrisman et al, 2005 ; Pütz et al, 2022 ; Weismeier-Sammer et al, 2013 ). The research literature shows that family firms have higher CSR levels (e.g., Dyer & Whetten, 2006 ; Liu et al, 2017 ; Singal, 2014 ), and we propose that this phenomenon is mainly rooted in the familiness effect where family resources (i.e., financial, human, and social capital) are provided by the owning family (Danes et al, 2008 ; Weismeier-Sammer et al, 2013 ) for the benefit of the firm and the family.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The integration of BDA into RC can yield enhanced stakeholder connections, heightened trust, and competitive benefits, as elucidated by DCT (Alkhatib and Valeri, 2022). Organizations that develop and enhance their dynamic capabilities in utilizing BDA are more effectively situated to negotiate intricate and ever-changing connections with stakeholders in the contemporary business environment (Pütz et al, 2023).…”
Section: The Mediating Role Of Relational Capitalmentioning
confidence: 99%